Effect Nigella sativa extract for balancing immune response in pristane induced lupus mice model - Theofilus Guritno, Wisnu Barlianto, Desy Wulandari, Winna Adelia Amru (Journal of Applied Pharmaceutical Science, 2021)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with wide manifestations that require long-term treatment. Current treatment has not shown a satisfying result and still yields some side effects. Nigella sativa (NS) has anti-inflammatory and immunomodulatory effects and thus has the potential to improve SLE symptoms. This study aims to understand the NS effect on the level of anti-dsDNA and Treg percentage in pristane-induced lupus (PIL) mice. Anti-dsDNA has an important role in diagnosing and prognosing SLE with high specificity. Treg has been known to be disturbed in SLE. This is a true experimental, randomized posttest only controlled group design with 25 female Bagg and Albino/c mice as the subject, divided into five groups: negative control/K(−)/healthy mice, positive control/K(+)/PIL mice, and three treatment groups (three different doses of NS, 1.2, 2.4, and 4.8 g/kgBW/day). AntidsDNA analysis was conducted using enzyme-linked immunosorbent assay and Treg using flow cytometry. Treatment group 4.8 g/kgBW/day has significantly lower anti-dsDNA and significantly higher Treg than K(+) (p < 0.01). Linear regression test showed that escalation of NS dose is correlated with the decrease of anti-dsDNA and increase of Treg in PIL mice. Thus, NS has the potential to repair the immune function in SLE.
Keywords: Nigella sativa, SLE, antidsDNA, Treg